APPLICATION OF INFORMATION TECHNOLOGY FOR PROMOTION AND SUSTAINABLE MANAGEMENT IN MARINE ECOTOURISM: A CASE STUDY IN BANGSRING, BANYUWANGI - Nurin Hidayati (Journal of Innovation and Applied Technology, 2016)
Ecotourism is a form of tourism management by promoting the unique tourist attraction such as natural destination, conservation, education and local wisdom. Banyuwangi is a region that makes ecotourism as an important pillar of the economy in coastal areas. Communities in the coastal village of Bangsring District, Banyuwangi, generally have a chance to earn more revenue from ecotourism sector. The existence of coral reefs and beautiful islands are natural potential that can be developed into high-value marine ecotourism, especially with the increase in ecotourism trend. It is also in line with the direction of Government policy in Banyuwangi to advance marine ecotourism sector. Based on information obtained from the chairman of Pokwasmas Samudera Bhakti and KNIH Bangsring, the problem faced by partners related to the development of ecotourism was that Bangsring ecotourism requires more promotions. Information about ecotourism so far has not fully use information technology, whereas characteristics of ecotourism fans who belong to a niche market requires their websites and other social media as an effective media campaign. "Bunder" (Underwater Bangsring) is one of the marketing strategies and promotion of village tourism potential in Bangsring using mobile application based on android. By using information technology (IT), “Bunder” is able to generate informations based on android platform that can be accesed from anywhere and by everyone. A downloadable application named "Bunder" is regarding the potential of tourism and natural resources in Bangsring and its surrounding. This application is expected to support effective promotion towards sustainable management of marine ecotourism in Bangsring, Banyuwangi.